Preparations, characterization, and biological features of mononuclear Cu(II) complexes based on hydrazone ligands. Issue 20 (15th October 2016) - Qin, Jie; Zhao, Shan-Shan; Liu, Ya-Ping; Man, Zhong-Wei; Wang, Peng; Wang, Li-Na; Xu, Yu; Zhu, Hai-Liang
Graphical abstract: Abstract: Three mononuclear Cu(II) complexes Cu(HL 1 )Cl2 (1 ), Cu(HL 2 )Cl2 (2 ), and Cu(L 3 )SCN (3 ) have been synthesized based on chelating hydrazone ligandsHL 1, HL 2, andHL 3, respectively. These new compounds gave satisfactory IR-spectroscopic data and were further characterized by elemental and X-ray diffraction analyses. Their urease inhibitory evaluation was tested in vitro against jack bean urease. The results showed that the inhibitory activities of the copper complexes are all superior to the positive reference. Enzyme kinetics studies were undertaken to estimate the inhibition mechanism of the copper complexes. Molecular docking simulations have been performed to rationalize their binding models. In addition, their interactions with serum albumin were also studied.